Strategi Diplomasi Vaksin Indonesia di Masa Pandemi Covid-19 Dalam Kerjasama Kesehatan Global (Mediasi: Journal of International Relations)
Indonesia's vaccine diplomacy during the Covid-19 pandemic was motivated by the threat of the deadly Covid-19 virus. Various countries in the world have made efforts to stop the spread of the Covid-19 virus. The death rate, which continues to increase daily, has caused the Covid-19 virus to be designated a Global Pandemic by WHO. As with other countries, this pandemic has encouraged Indonesia to cooperate in health in dealing with the virus outbreak. Vaccines, as the main control, play an important role in stopping the spread of the Covid-19 virus and are experiencing problems in supply and distribution to various countries. This variable is the background for Indonesia to carry out vaccine diplomacy cooperation. This study uses a descriptive qualitative method, with data obtained from libraries, government agencies, and international organizations, as well as from various journals and mass media sources. Indonesia's vaccine diplomacy is carried out in multilateral forums as a forum for Indonesia's strategic instruments in diplomacy. In this program, Indonesia voiced